Social Media Influence on Enhancing EFL Learners’ Speaking Skills - Khuluod Mohammed Labaidi (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2024)
This research paper explores the impact of using social media on improving English speaking skills as a Foreign Language (EFL), with a specific focus on students at the Faculty of Languages at Benghazi University in all branches. The study aims to investigate how the integration of social media platforms, such as Facebook, Instagram, Telegram and Twitter, can enhance EFL learners’ speaking proficiency. Also, the research employs a case study approach to gather quantitative data from EFL students at the Faculty of Languages at Benghazi University. The findings of this study will contribute to the existing literature on language learning and technology integration, providing insights into the potential benefits and challenges of using social media to improve EFL speaking skills. This research has implications for language educators, curriculum developers, and policymakers seeking to enhance language learning opportunities through digital platforms.